Podcast sebagai Alternatif Distribusi Konten Audio - Fadilah, Efi; Yudhapramesti, Pandan; Aristi, Nindi (Jurnal Kajian Jurnalisme, 2017)
The proliferation of Internet has been another warning bell for conventional broadcast radio. Numbers of listener gradually shift to the new mean of media as it is more attractive and convenient  for users. The situation drives radio managers to adapt with various ways. Developing audio podcast is among the strategy that has been growing in the United States and various countries in Europe, but not yet quite popular in Indonesia. Whereas the potential audience is quite large, since the growing number of commuters and fact that about 30% of total population is categorized as auditory learner. For such reason, this library research is conducted to explore the opportunities for audio podcast to develop in Indonesia, as well as content analysis of some of the most successful podcast provider sites. The results show that audio podcast optimization strategy includes the development of podcast materials with appropriate approach and content distribution with audience’s needs, wants, and ways of consuming audio content; as well as the compatibility of the content with the character and orientation of the media. In addition, this effort must also be accompanied by intensive campaigns through various way.